Churchill and Roosevelt. - Kimball, Warren F. (Princeton Legacy Library, 2016)
The complete correspondence of Winston Churchill and Franklin D. Roosevelt. Including every written communication that passed between Churchill and Roosevelt during the five and a half years of their wartime leadership, this body of material is essential to an understanding of the politics and strategy of World War II as conducted by two of history's most charismatic men. Volume II covers the period from November 15, 1942 through February 29, 1944. Originally published in 2015. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.